The Association Between Frequent Sugar-Sweetened Beverage Intake and Sleep Duration in School Children: A Cross-Sectional Study - Shih, Ya-Hui; Wu, Hsin-Chuan; Pan, Wen-Harn; Chang, Hsing-Yi (Frontiers in Nutrition, 2022)
Background: Higher consumption of sugar-sweetened beverages (SSBs) maybe association with children’s sleep pattern. However, few studies have considered this association in Asia, especially in school children. This study investigated the relationship between children’s consumption frequency of such beverages and their sleep duration. Methods: Participants aged 6-12 years were analysed from two survey data in 2012 and 2013-2016 Nutrition and Health Surveys in Taiwan. A total of 2628 participants were included in the analysis (2012, N=1267; 2013-2016,，N=1361). Beverages weekly consumption were divided into low and high intake groups by medians cut-off points. The sleep variables were the sleep duration at night (including school days and weekends) and sleep debt. After controlling the confounders, the correlation between sugar-sweetened beverage consumption and sleep duration was examined using multinomial logistic regression analysis. Results: The students slept for an average of 8.8 h on school days and 9.7 h on weekends. Relative to the low SSB intake group, the high intake group exhibited shorter sleep durations on school days (P < 0.001), greater sleep debt (P = 0.049). In logistic regression, high intake group were more likely to sleep for <8.5 h on school days (OR= 1.67, P = 0.002) and exhibit >2 h of sleep debt than low intake group (OR = 1.41, P = 0.022). Conclusions: Children who had consumed sugar-sweetened beverages frequently slept for shorter durations at night on school days and exhibited greater sleep debt. The causal relationship was not clear. Nonetheless, these two factors are important in promoting children health.